Diameter of alveolar antral artery in the lateral sinus wall: study of related factors. Issue 4 (May 2017) - Varela-Centelles, P.; Seoane, J.; Loira-Gago, M.; González-Mosquera, A.; Seoane-Romero, J.M.
Abstract: To identify the variables that influence the diameter of the artery in the lateral sinus wall, we studied 240 sinuses, focusing on sex, pattern of tooth loss, type of residual crest, thickness of the lateral wall, height and width of the ridge, and width of the sinus.